The Status and Future of Korean Computer-aided Publishing Industry: focused on the publishing markets - OH, LEE JONG (Advances in Social Sciences Research Journal, 2018)
In the present article, we analyze Korean computer-aided publishing (CAP) market which is growing large in the digital age. Since the Korean market is reorganized into various areas, we examine current conditions and issues of it and discuss several suggestions for the development of Korean CAP industry. The main issues of Korean CAP industry are the conventional images concerning publication, the lack of human resources specialized in CAP, and insufficient platform or viewer for E-books. Grounded on the research results, we suggest five points to develop Korean publication industry. Endeavor of publishing circle is required for the most. The government should reflect the issues and suggestions to the policies and also publishing circle should work with the government with positive and future-oriented attitude.